High mobility group A1 (HMGA1) promotes esophageal squamous cell carcinoma progression by inhibiting STING-mediated anti-tumor immunity - Kai-Yue He; Annie Zhao; Jin-Rong Guo; Dan-Hui Wu; Huai Liu; Fan Gao; Meng-Jie Liu; Jing-Yu Yang; Xin-Yuan Lei; Jun-Qi Li; Lei Zhang; Zhen-Hua Yan; et al. (Nature Communications)
Abstract Esophageal squamous cell carcinoma (ESCC) is a common and aggressive cancer with limited responses to immunotherapy. High mobility group A1 (HMGA1), a chromatin remodeling protein, plays a key role in tumor progression, but its impact on anti-tumor immunity in ESCC remains unclear. Here we show that HMGA1 suppresses the stimulator of interferon genes (STING), inhibiting type I interferon secretion, downregulating interferon-stimulated genes, and impairing tumor-infiltrating lymphocyte (TIL) recruitment. HMGA1 inhibits STING transcription by competing with the coactivator CBP/p300 for binding to CREB. ESCCs from genetically modified mouse models with altered HMGA1 and STING expression exhibit varying TIL levels and sensitivity to STING agonists. Additionally, we design and synthesize a series of HMGA1 inhibitors, including a perylene-based nanoparticle, PDIC-DPC, which effectively inhibits HMGA1 and enhances TIL infiltration. Our findings identify HMGA1 as a critical immune checkpoint in ESCC and suggest that targeting HMGA1 could improve immunotherapy outcomes.